Invoking rules in everyday family interactions: a method for appealing to practical reason - Küttner, Uwe-Alexander; Vatanen, Anna; Zinken, Jörg (Human studies, 2022)
In this article we examine moments in which parents or other caregivers overtly invoke rules during episodes in which they take issue with, intervene against, and try to change a child’s ongoing behavior or action(s). Drawing on interactional data from four different languages (English, Finnish, German, Polish) and using Conversation Analytic methods, we first illustrate the variety of ways in which parents may use such overt rule invocations as part of their behavior modification attempts, showing them to be functionally versatile interactional objects. Their interactional flexibility notwithstanding, we find that parents typically invoke rules when, in the course of the intervention episode, they encounter trouble with achieving an acceptable compliant outcome. To get at the distinct import of rule formulations in this context, we then compare them to two sequential alternatives: parental expressions of an experienced negative affective state, and parental threats. While the former emphasize aspects of social solidarity, the latter seek to enforce compliance by foregrounding a power asymmetry between the parent and the child. Rule formulations, by contrast, are designedly impersonal and appear to be directed at what the parents construe as shortcomings in common-sense practical reasoning on the child’s part. Reflexively, the child is thereby cast as not having properly applied common-sense ‘practical reason’ when engaging in what is treated as the problematic behavior or action. Overt rule invocations can, therefore, be understood as indexical appeals to practical reason.
Online veröffentlicht: 15. November 2022
Gesehen am 14.03.2025